Review of the efficacy of low emission zones to improve urban air quality in European cities. (June 2015) - Holman, Claire; Harrison, Roy; Querol, Xavier
Abstract: Many cities still exceed the European Union (EU) air quality limit values for particulate matter (PM10, particles with an aerodynamic diameter less than 10 μm) and/or nitrogen dioxide (NO2 ). In an attempt to reduce emissions approximately 200 low emission zones (LEZs) have been established in 12 EU countries. These restrict the entry of vehicles based on the emission standard the vehicles were originally constructed to meet, but the restrictions vary considerably. This paper reviews the evidence on the efficacy of LEZs to improve urban air quality in five EU countries (Denmark, Germany, Netherlands, Italy and UK), and concludes that there have been mixed results. There is some evidence from ambient measurements that LEZs in Germany, which restrict passenger cars as well as heavy duty vehicles (HDVs), have reduced long term average PM10 and NO2 concentrations by a few percent. Elsewhere, where restrictions are limited to HDVs, the picture is much less clear. This may be due to the large number of confounding factors. On the other hand there is some, albeit limited, evidence that LEZs may result in larger reductions in concentrations of carbonaceous particles, due to traffic making a larger contribution to ambient concentrations of these particles than to PM10 and PM2.5 . The effects of day to day variations in meteorology on concentrations often mask more subtle effects of a LEZ. In addition, separating the direct effects of a LEZ from the effects of other policy measures, the economy and the normal renewal of the vehicle fleet is not easy, and may give rise to false results. Highlights: Most studies of LEZs have not taken confounding factors into account adequately. German LEZs may have reduced PM10 and NO2 concentrations by a few percent. Elsewhere no clear effects on PM10 and NO2 observed. Carbonaceous particle concentrations may be reduced significantly.